Bleeding Risk in Patients Using Oral Anticoagulants Undergoing Surgical Procedures in Dentistry: A Systematic Review and Meta-Analysis - Andrade, Natália Karol de; Motta, Rogério Heládio Lopes; Bergamaschi, Cristiane de Cássia; Oliveira, Luciana Butini; Guimarães, Caio Chaves; Araújo, Jimmy de Oliveira; Lopes, Luciane Cruz (Frontiers in Pharmacology, 2019)
The management of patients who undergo dental surgical procedures and receive oral anticoagulant therapy requires particular attention due to the risk of bleeding that may occur during the procedure. Bleeding rates in these trans- or post-operative patients tend to be unpredictable. The aim of this study was to conduct a systematic review in order to assess the risk of bleeding during and after performing oral surgery in patients administered oral anticoagulants compared with a group that discontinued anticoagulant therapy. For the purposes of this review, we searched the databases of the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (via Ovid), EMBASE (via Ovid), and the Virtual Health Library (VHL) from inception of the database to December 2018. The primary outcome was defined as the occurrence of local bleeding during and after oral surgical procedures. Four reviewers, independently and in pairs, screened titles and abstracts for full-text eligibility. Data regarding participant characteristics, interventions, and design and outcomes of the included studies were extracted. The data were pooled using random-effects meta-analyses and described as risk ratios (RRs) with a 95% confidence interval (95% CI). The confidence for the pooled estimates was ascertained through the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach, and the protocol of this review was recorded in PROSPERO (CRD42017056986). A total of 58 eligible studies were identified, of which three randomized controlled trials were included in the meta-analysis, covering a total of 323 adult participants, among whom 167 were taking anticoagulants at the time they underwent dental surgery. Of these patients, 14.2% had reported bleeding. The risk of bleeding was found to be one to almost three times greater in patients taking warfarin compared with patients who discontinued the use of anticoagulant during the trans-operative period (RR = 1.67, 95% CI = 0.97 to 2.89) and in the post-operative period (RR = 1.44, 95% CI = 0.71 to 2.92), although the quality of evidence was very low. The results indicate that there is no evidence that the use of anticoagulants eliminates the risk of bleeding during surgical dental procedures.